2016
DOI: 10.1016/j.ultramic.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Dopant profiling based on scanning electron and helium ion microscopy

Abstract: Highlights• Strong doping contrast from n-type regions in the SHIM without energy-filtering.• Sensitivity limits are established of the SHIM and SEM techniques.• We discuss the impact of SHIM imaging conditions on quantitative dopant profiling.• Doping contrast stems from different surface layer thicknesses in the SHIM and SEM.In this paper, we evaluate and compare doping contrast generated inside the scanning electron microscope (SEM) and scanning helium ion microscope (SHIM). Specialised energy-filtering tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Defect localisation within conductive structures at the nano-scale (sub-10 nm), while minimising the damage applied to the analysed zone, can be performed within the HIM by using the voltage contrast mechanism [22]. Another effect that comes into play for investigations of semiconductors is the static capacitive effect, which is used to reveal dopant concentration changes even if quantification remains challenging [23,24]. An application, in which the electron flood gun has demonstrated its usefulness, has been reported by Baggott et al [25] for imaging ceramic silicon nitride samples.…”
Section: Applicationsmentioning
confidence: 99%
“…Defect localisation within conductive structures at the nano-scale (sub-10 nm), while minimising the damage applied to the analysed zone, can be performed within the HIM by using the voltage contrast mechanism [22]. Another effect that comes into play for investigations of semiconductors is the static capacitive effect, which is used to reveal dopant concentration changes even if quantification remains challenging [23,24]. An application, in which the electron flood gun has demonstrated its usefulness, has been reported by Baggott et al [25] for imaging ceramic silicon nitride samples.…”
Section: Applicationsmentioning
confidence: 99%
“…in the region where SEs are emitted from. This improves the spatial resolution in HIM compared to scanning electron microscopy (SEM) [10,11]. It was also shown that the SE emission in HIM is more sensitive to the surface electronic variations compared to SEM, which makes HIM more suitable compared to SEM for dopant profiling with improved sensitivity and spatial resolution [12].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of helium ion microscopy (HIM) has further improved the spatial resolution and sensitivity of dopant profiling using SE imaging [7][8][9][10][11]. HIM produces a smaller spot size owing to the atomically sharp ion source and lower de Broglie wavelength (due to the heavier ion mass).…”
Section: Introductionmentioning
confidence: 99%
“…Such domains are no longer visible when sputter coated with 10 nm gold layers to make them conductive for SEM analysis . The HIM has also been used for imaging of dopant profiles in semiconductor materials and visualization of the conductivity of graphene layers . Channelling contrast (both in SE and BSI modes) has been used to determine crystallographic orientation in gold films. , The high resolution milling capabilities of helium have been used to fabricate a wide range of nanoscale structures/devices, including nanopores for biomolecule identification, graphene nanodevices, ,, nanostructured silicon nitride membranes, and nanophotonic structures with smaller feature sizes and improved optical properties. The addition of neon has extended the milling/machining capabilities of the tool by providing increased milling rates and lower implantation and subsurface damage.…”
mentioning
confidence: 99%
“…Such domains are no longer visible when sputter coated with 10 nm gold layers to make them conductive for SEM analysis. 14 The HIM has also been used for imaging of dopant profiles in semiconductor materials 15 and visualization of the conductivity of graphene layers. 16 Channelling contrast (both in SE and BSI modes) has been used to determine crystallographic orientation in gold films.…”
mentioning
confidence: 99%